Influence of cerium triflate and glycerol on electrochemical performance of chitosan electrolytes for electrochromic devices - Alves, Raquel Diana Carneiro (2016)
Polymer electrolytes based on chitosan, glycerol, and cerium triflate are prepared by solution casting technique, and their properties are studied by complex impedance spectroscopy, thermal analysis (DSC and TGA), scanning electron microscopy (SEM), X-ray diffraction (XRD), and atomic force microscopy (AFM). The concentration of cerium triflate ranges between 0.00 and 55.72 wt%. The DSC results reveal a thermal event between 128 and 145ºC indicating a semi-crystalline nature of the samples. The best ionic conducting values of 1.46×10-6 and 8.74×10-5 S cm-1 at 30 and 90ºC, respectively are registered for the sample containing 33.32 wt% of salt. Moreover, it is stated that an increase of glycerol amount promotes an increase of the ionic conductivity up to maximum values of 1.67x10-5 and 4.93x10-4 S cm-1 at 30 and 90 ºC, respectively. SEM images show clusters formation for samples with high salt concentration, and X-Ray studies point a disappearance of large peak at 2θ ≈ 20º and appearance of narrow one at 2θ ≈ 10º, confirming crystalline domains formation. AFM results display the morphological characteristics of samples and 3.72 nm was the value obtained for the sample with less roughness.